Cell Biology and Translational Medicine, Volume 1 Stem Cells in Regenerative Medicine: Advances and Challenges (Cell Biology and Translational Medicine,, 2018)
Much research has focused on the basic cellular and molecular biological aspects of stem cells. Much of this research has been fueled by their potential for use in regenerative medicine applications, which has in turn spurred growing numbers of translational and clinical studies. However, more work is needed if the potential is to be realized for improvement of the lives and well-being of patients with numerous diseases and conditions. With a goal to accelerate advances by timely information exchange, this new book series 'Cell Biology and Translational Medicine (CBTMED)' as part of SpringerNature's longstanding and very successful Advances in Experimental Medicine and Biology book series is launched. Emerging areas of regenerative medicine and translational aspects of stem cells will be covered in each volume. Outstanding researchers are recruited to highlight developments and remaining challenges in both the basic research and clinical arenas. This current book is the first volume of a continuing series.